Pemberdayaan Masyarakat: Konsep, Peluang, dan Tantangan dalam Perspektif Islam - Fatkhullah, Mukhammad; Habib, Muhammad Alhada Fuadilah (Universitas Negeri Surabaya, 2023)
Community empowerment is a solution to manage public funds. This article aims to look at the history, basic principles, actors, vulnerable groups, opportunities and challenges of community empowerment through an Islamic perspective. Using a qualitative approach with library research methods, article utilizes the Qur'an and hadith as primary data, as well as other literature such as books and relevant journals as secondary data, then analyzed througj maudhu'i technique. The principle of society in Islam is centered on 3 main principles, namely brotherhood (ukhuwah), the principle of mutual assistance (ta'awun), and the principle of justice or equality. The nature of empowerment is in line with da'wah, it can be done individually (fardiyah), or collectively (jam'iyah), by providing the community with the ability to make changes. The changes referred to in Islam have four characteristics: (1) changes that are collective, not individualistic, (2) non-discriminatory and non-Islamic-centric, (3) in line with God's will, and (4) prioritizing character changes. People who need to be empowered are called mustad'afin, which includes: the needy, the poor, widows, orphans, and people who are struggling in the way of Allah. The community empowerment can be implemented through activities that are religious in nature or activities that are muamalah.